Disentangling effects of structure and knowledge in perceiving partly occluded shapes: An ERP study. (September 2016) - Hazenberg, Simon J.; van Lier, Rob
Abstract: Using event-related potentials (ERPs) we investigated the influence of object knowledge on perceiving partly occluded shapes. We created stimuli based on well-known objects of which the middle part was occluded. Object completions that were compatible with structure consisted of the connection of the visible fragments by smoothly extending their contours. In contrast, object completions that were incompatible with structure consisted of separate disconnected completions of the fragments. Furthermore, object completions could be in line with, or conflict with expectations based on knowledge. We measured ERPs when hidden parts were revealed by removing the occluder, and observed an early positive ERP peaking around 115–140 ms at occipital sites, presumably triggered by physical differences. Most importantly, we observed a positive ERP peaking around 300–400 ms at parieto-occipital sites that could be related to influences of both structure and knowledge. An additional analysis controlling for differential stimulus characteristics revealed similar conclusions. All in all, we demonstrate that the interpretation of partly occluded shapes is not solely driven by stimulus structure, but that it can also be influenced by knowledge of objects.